Mortality pattern in cirrhosis: A reflection of liver disease burden in India. Issue 6 (18th October 2021) - Misra, Debashis; Das, Kausik; Chatterjee, Saswata; Mukherjee, Parthasarathi; Chowdhury, Abhijit
Summary: Introduction and objective: Mortality data from high‐income group countries are frequently used in developing countries for healthcare planning. This study was planned to explore the mortality pattern of cirrhosis in India in terms of survival after diagnosis of cirrhosis, predictors of death and aetiology specific effect on mortality. Methods: This observational study enrolled newly diagnosed patients with liver disease (n = 3193) attending a tertiary care hospital in Kolkata, India between April 2010 and October 2012 and were followed up to September 2015. Results: Patients with cirrhosis having complete follow‐up data (n = 702) were analysed. Median follow‐up duration was 21 months (range: 1‐84 months). Mortality among them was 51% (n = 358 out of 702). Development of HCC (OR 2.8: 95%CI 1.8‐4.2, P < 0.0001), male gender (OR 1.4: 95% CI 1.0‐1.8, P = 0.009) and higher Child score at the time of diagnosis (OR 1.2: 95%CI 1.1‐1.3, P < 0.0001) were predictors of mortality. Survival after the diagnosis of cirrhosis was significantly shorter in alcohol (16.5 month; range 1‐51)‐ and HCV (16 month; range 1‐48)‐related cirrhosis in comparison to HBV (23 month; range 1‐48)‐related and cryptogenic cirrhosis (22 month; range 1‐84) ( P = 0.014). Conclusion: Majority of the patients with cirrhosis had decompensation at the time of diagnosis. Shorter survival was noticed in alcohol‐ and HCV‐related cirrhosis.